Knowledge and attitudes toward breastfeeding among female university students in Tabuk, Saudi Arabia - Reham Khresheh (Kashan University of Medical Sciences, 2020)
Background: In Saudi Arabia, rates and duration of breastfeeding are progressively declining. Objective: The objective of this study was to examine and describe the relationship between breastfeeding knowledge, attitudes, exposure, and intention of university female students in Saudi Arabia. Methods: This cross-sectional survey recruited 124 students who completed a self-reported questionnaire. The questionnaire included breastfeeding knowledge, attitude and exposure scales, and a breastfeeding intention scale. Descriptive and inferential statistics were used to analyze the data. Results: Participants had good breastfeeding knowledge (mean score of 9.51 ± 2.63) and positive attitudes (mean score of 42.0 ± 1.8). However, they had some misconceptions about eating certain foods during breastfeeding and that breastfeeding is painful. A significant relationship was found between breastfeeding knowledge and attitude (r = 0.896,P <0.01), breastfeeding knowledge and exposure (r = 0.191,P <0.01), breastfeeding knowledge and intention to breastfeed (Phi coefficient=0.179, P = 0.033), and breastfeeding attitudes and intention to breastfeed (Phi coefficient=0.177, P = 0.030). Participants' knowledge (OR=3.280;P <0.001) and attitude (OR=1.930;P <0.001) were identified as factors independently and positively associated with future breastfeeding intention. Conclusion: The study identified specific gaps in knowledge and attitudes that pertain mainly to breastfeeding in public and perceptions that breastfeeding is painful, formula feeding gives more freedom to the mother, and that dietary restrictions by the mother during breastfeeding are needed. These gaps should be addressed in future breastfeeding promotion.